Karakteristik Penderita Katarak Senilis di Rumah Sakit Umum Daerah Tabanan Tahun 2023 - Ni Kadek Inka Widyasastrawati; Pande Ayu Naya Kasih Permatananda; I Putu Rustama Putra (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2025)
Cataract is a cause of visual impairment and blindness in the world with a percentage of 25.81%. Cataract sufferers in Bali Province are the 3rd highest after North Sulawesi, Jambi, and Aceh. Tabanan Regency is in third place after Gianyar and Denpasar Regencies with a cataract percentage reaching 17.20%. Cataracts caused by age or aging factors are called senile cataracts. This study aims to analyze the characteristics of senile cataract sufferers at Tabanan Regional Hospital using a descriptive research design and a cross-sectional approach. The data collection method uses inclusion and exclusion criteria. Inclusion criteria include patients diagnosed with cataracts at Tabanan Regional Hospital in January-December 2023 and patients aged >50 years. Exclusion criteria include medical record data that does not contain demographic data, age, and gender, clinical data such as visual acuity, stage, diagnosis, and management, and unreadable medical record data. Based on the research, it can be concluded that the characteristics of senile cataract patients at Tabanan Regional Hospital in 2023 were the highest age group in the 55-65 year age group at 39,8%, gender was higher in women at 61,4%, comorbidities such as hypertension were 8,4% and DM was 6%, the highest stage was the immature stage at 88%, the patient's vision was highest in poor vision at 51,8% and based on the management given to senile cataract patients phacoemulsification at 81,9%. It is hoped that the results of this study can be a reference for further research, and become the basis for preventive and promotive efforts for cataracts in the elderly.